2009
DOI: 10.1111/j.1538-7836.2008.03249.x
|View full text |Cite
|
Sign up to set email alerts
|

The activation peptide of thrombin‐activatable fibrinolysis inhibitor: a role in activity and stability of the enzyme?

Abstract: Summary. Background: Thrombin-activatable fibrinolysis inhibitor (TAFI) is a 56-kDa procarboxypeptidase. Proteolytic enzymes activate TAFI into TAFIa, an inhibitor of fibrinolysis, by cleaving off the N-terminal activation peptide (amino acids 1-92), from the enzyme moiety. Activated TAFI is unstable, with a half-life of approximately 10 min at 37°C. So far, it is unknown whether the activation peptide is released or remains attached to the catalytic domain, and whether it influences TAFIaÕs properties. The cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 18 publications
2
29
0
2
Order By: Relevance
“…Because of the relatively long plasma half-life of PAI-1 activity (approximately 1 h), antigen and activity measurements might go hand in hand in healthy subjects. However, the poor correlation between measurements of TAFI-Ag and activity might be because activated TAFI is quickly inactivated by a rapid spontaneous conversion to the latent form with a half-life of approximately 10 min (83). Therefore, the very short half-life of TAFIa presents a practical measurement problem, which is difficult to overcome in clinical settings (84).…”
Section: Plasma Pai-1/tafi Measurements Do Not Reflect Endogenous Thrmentioning
confidence: 99%
“…Because of the relatively long plasma half-life of PAI-1 activity (approximately 1 h), antigen and activity measurements might go hand in hand in healthy subjects. However, the poor correlation between measurements of TAFI-Ag and activity might be because activated TAFI is quickly inactivated by a rapid spontaneous conversion to the latent form with a half-life of approximately 10 min (83). Therefore, the very short half-life of TAFIa presents a practical measurement problem, which is difficult to overcome in clinical settings (84).…”
Section: Plasma Pai-1/tafi Measurements Do Not Reflect Endogenous Thrmentioning
confidence: 99%
“…However, this was challenged by Marx et al . , who separated TAFIa from the activation peptide, and demonstrated that the activation peptide had no effect on TAFIa's activity or stability. The deletion mutant constructed by Zhou et al .…”
mentioning
confidence: 99%
“…It was suggested that this interaction might affect TAFIa activity. However, this was challenged by Marx et al [18], who separated TAFIa from the activation peptide, and demonstrated that the activation peptide had no effect on TAFIa's activity or stability. The deletion mutant constructed by Zhou et al lacks most of the activation peptide, and makes it ideal for this debate.…”
mentioning
confidence: 99%
“…Immediately after TAFI activation, H‐D‐Phe‐Pro‐Arg‐chloromethylketone (PPACK, 1 μ m ) was added to inhibit thrombin activity and TAFIa activity was measured using the method developed by Willemse et al . as previously described . The Michaelis‐Menten constants were determined by using non‐linear regression in Graphpad Prism version 5.01 (Graphpad, San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…For the determination of the Michaelis-Menten constants (V max , K M and V max /K M ), TAFI (31-2000 nM) was added to a premix of thrombin (8 nM), thrombomodulin (16 nM) and CaCl 2 (5 mM) in the absence or presence of pure peptide 2 (50 lM), peptide 18 (250 lM), peptide 19 (700 lM), peptide 29 (700 lM) or peptide 34 (10 lM) for 1 min at RT. Immediately after TAFI activation, H-D-Phe-Pro-Arg-chloromethylketone (PPACK, 1 lM) was added to inhibit thrombin activity and TAFIa activity was measured using the method developed by Willemse et al [16] as previously described [15]. The Michaelis-Menten constants were determined by using non-linear regression in Graphpad Prism version 5.01 (Graphpad, San Diego, CA, USA).…”
Section: Tafi Activationmentioning
confidence: 99%